Karakteristik Mutu Kaki Naga Ikan Nila Dengan Substitusi Tepung Mocaf Sebagai Produk Diversifikasi - Vatria, Belvi; Primadini, Vivin; Kusumawati, Rr. Puji Hastuti (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2024)
Tilapia dragon feet are processed fish products that are currently developing. The combination of tilapia meat and mocaf flour can create dragon feet products with delicious taste, high nutrition, affordable price, and good for health. The purpose of this study was to describe the quality characteristics of tilapia dragon feet substituted with mocaf flour and to describe the best formulation of tilapia dragon feet with mocaf flour substitution. This study conducted an experiment using a one-factor completely randomized design (CRD) model with four levels. The factors tested were the substitution between tilapia meat and mocaf flour of 5%, 10%, 15%, and 20%. The substitution was calculated from the total weight of 100% (meat + mocaf flour). Parametric analysis used the F test in Anova. Non-parametric analysis used the Kruskal-Wallis test. This study found that the physical test of dragon fish feet, which includes a bite test obtained a value ranging from 6.15 - 6.42 (scale 9), a folding test of 3.45 - 3.83 (scale 5), gel strength ranging from 232.17 g.cm - 245.38 g.cm, water binding capacity ranging from 72.27% - 73.12%, and emulsion stability of 72.22% - 72.87%. The hedonic test of tilapia dragon fish feet which includes color obtained a value ranging from 6.21-7.39, aroma 7.89 - 7.81, texture 7.12 - 7.89, taste 6.95 - 7.66 and appearance 7.15 - 7.26. The chemical and microbiological quality characteristics of all dragon fish feet formulations still meet SNI quality standards. With physical quality characteristic specifications such as gel strength of 232.17 grams per centimeter, water binding capacity of 72.27%, and emulsion stability of 72.22%, formulation A1 is the best based on the panelists' preference level.